The Micro Skill of Conducting Variability by Student Teachers Attending a Preparatory Course for Teaching Practice Program - Sri Wahyuni (Departement of Mathematics Education, 2023)
Educating student teachers to become exciting and dynamic teachers requires intensive practice to focus on the micro-skill components. To create exciting and dynamic teachers, student teachers need to improve their skill of variability. There are three types of skill variation: variation in the teacher’s manner and style, variations in the media and materials of instructions, and interaction and activity variation. The variation in the teacher’s manner includes voice, gesture, pausing, eye contact, movement, and verbal marker. While for the variation in media and material of instruction, there are visual, aural, and tactile variations. Teachers can change the interaction pattern with the students for interaction and activity variation. This paper focused on analyzing the student teachers’ performance in teaching practice classes in conducting variation in teacher’s manner and style. The class consisted of 20 students preparing for teaching in Senior High School. All their performance was video recorded. Then this recording was analyzed using the component of skill of variability. At the end of the practice session, students reflected on their practice in class. This way, student teachers prepare themselves to become teachers aware of making interesting classroom situations.